Future trends in housing tenure and the adequacy of retirement income - Rachel Slaymaker; Barra Roantree; Anne Nolan; Conor O'Toole (The Economic and Social Research Institute (ESRI), 2022)
In recent years, Ireland has experienced a notable decline in homeownership and a rise in the proportion of households in private rental accommodation. Concurrently, the cost of both rents and house prices have risen markedly and affordability challenges in terms of meeting housing costs have been well documented. While these challenges are immediate in terms of the housing costs burden, a longer-term issue arises as to how renting households will manage the financial adjustment to retirement with ongoing rent payments. This transition historically in Ireland has been smoothed by high homeownership rates and mortgage amortisation which lowered the cost of housing payments and increased financial assets. Indeed, existing international evidence suggests that being a homeowner can provide a 'double dividend' of lowering housing costs and increasing assets in retirement. This can help manage changes to income in retirement and allow households to maintain their standard of living. The continued requirement to cover housing costs for renters in retirement can be seen as an additional vulnerability in terms of retirement income adequacy in Ireland, over and above the general concern of sufficient pension income. While considerable research to date has documented this well-known challenge of providing a sufficient standard of living in retirement for many households in Ireland, the drop in the homeownership rate layers an additional complication in terms of the policy challenge. To address these related issues, this report explores indicative future paths for homeownership rates in Ireland and explores the impact in terms of income poverty in retirement. Using data from the Survey on Income and Living Conditions (SILC) and the Irish Longitudinal Study on Ageing (TILDA), we consider a number of scenarios to assess the possibility of renting households becoming homeowners, and then test the impact on income poverty rates if households were to continue to have rental costs into retirement.
Keywords: 330; Besitzformwahl; Wohneigentum; Mietwohnung; Rentner; Altersvorsorge; Wohnkosten; Wohneigentumspolitik; Irland